China's expansion into the western hemisphere implications for Latin America and the United States - Roett, Riordan, 1938-; Paz, Guadalupe, 1970- (Brookings Institution Press, 2008)
"Analyzes the history and motivations of U.S.-China-Latin America relationship. Focuses on China's growing economic ties to the region, including Latin America's role in China's search for energy resources. Highlights the geopolitical implications of Chinese hemispheric policy and sets recent developments in the context of China's role in the developing world"--Provided by publisher.